Connecting - Helen Walker; Laura Milner; Candace Walworth; Dave Waddell; Vic Kryston; Richard L. Graves (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Laura Milner—Steve's Story. Candace Walworth—War & Peace in a Two-Car Garage. Dave Waddell—Caring. Vic Kryston—Ralph and the Unexpected Fix. Richard L. Graves—The Abraham Dream.